Effects of post-meal resistance exercise on postprandial glycaemia in healthy young men - Soh, Douglas Yuhong (2018)
An unhealthy diet can contribute to elevated glucose concentrations in the body. The resultant metabolic stress due to elevated postprandial glycaemia (PPG) concentrations is a major risk factor for obesity, Type 2 diabetes and cardiovascular diseases. The most effective time to perform resistance exercise (RE) is limited with little studies done, while most other studies examined pre-meal RE. The aim of the present study was to examine the acute effects of post-meal RE on PPG concentrations. Ten healthy males age 24.9 (SD 1.1) years old completed two 1-d trials, RE and control, at least 1 week apart in a counterbalanced randomized design. In each trial, participants ingested a test meal (10.1kcal (42kJ) kg-1 body mass) and rested for 30 min before performing a 60 min bout of RE or remained inactive (control). Blood samples were collected and analyzed for PPG concentrations at baseline, 25, 120, 180 and 240 min. Postprandial glucose iAUC was 139% lower during RE trial compared to control trial (79.53 (118.85) vs 190.05 (143.72) mmol/L w 240 min, respectively; p = 0.038). The pattern of mean PPG concentrations was significantly different between trials over time: trial x time interaction (p = 0.043). Mean PPG concentration at 120 min was significantly lower on the RE compared to control trial (Holm-Bonferroni t-test, p=0.008). Results of this study indicate a single bout of RE performed during the postprandial period reduces PPG concentrations in healthy young men and support physical activity recommendations to perform RE regularly for better metabolic health.